Relationship among Perceived Usefulness, Ease of Use, Attitude and Intention to Use Emerging Technology among Undergraduate in South-West Nigeria - Keji, Sakiru Sulaimon (Journal for Lesson and Learning Studies, 2024)
Emerging technological tools are innovative and instructional tools used to supplement traditional teaching and learning for the enhancement of students' positive academic performance. Despite its instructional benefits, they have not been fully utilized for learning among undergraduates in Nigeria. Hence, the study analyzes the relationship among perceived usefulness, ease of use, attitude and intention to use Emerging Technology among undergraduate in South-west Nigeria. The study adopted quantitative research design of survey type. The population was all undergraduates’ students in south-west, Nigeria out of which a sample of 1,412 were purposively sampled from 12 Federal and State universities in South-west, Nigeria. Data were collected through the administration of validated researcher-designed questionnaire. Percentages and mean scores were used to answer the research questions, while independent t-test and Analysis of variance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. The findings indicated that there was no significant relationship among undergraduates perceived usefulness, ease of use, attitude and intention to use Emerging Technology in South-west Nigeria. The study concluded that Emerging Technological tools are better learning strategies for all undergraduates if well integrated in teaching and learning can help in improving undergraduates’ learning. The study recommended among others that undergraduates should be given the necessary supports on the provision of all needed facilities for proper utilization of the emerging technology for learning.